An exome‐wide exploration of cases of primary ovarian insufficiency uncovers novel sequence variants and candidate genes. Issue 3 (28th July 2020) - Alvarez‐Mora, Maria Isabel; Todeschini, Anne‐Laure; Caburet, Sandrine; Perets, Lilach Peled; Mila, Montserrat; Younis, Johnny S.; Shalev, Stavit; Veitia, Reiner A.
Abstract: Primary ovarian insufficiency (POI) implies the cessation of menstruation for several months in women before the age of 40 years and is a major cause of infertility. The study of the contribution of genetic factors to POI has been fueled by the use of whole exome sequencing (WES). Here, to uncover novel causative pathogenic variants and risk alleles, WES has been performed in 12 patients with familial POI (eight unrelated index cases and two pairs of sisters) and six women with early menopause and family history of POI (four index cases and one pair of sisters). Likely causative variants in NR5A1 and MCM9 genes were identified as well as a variant in INHA that requires further investigation. Moreover, we have identified more than one candidate variant in 3 out of 15 familial cases. Taken together, our results highlight the genetic heterogeneity of POI and early menopause and support the hypothesis of an oligogenic inheritance of such conditions, in addition to monogenic inheritance. Abstract :